Model Pembelajaran STAD melalui Media Kotak Kartu Misterius (KOKAMI): Penerapan terhadap Hasil Belajar Fisika SMP Materi Usaha dan Pesawat Sederhana - Desti Prastikawati; Siti Anisatur Rofiqah; Widayanti Widayanti (U-Teach: Journal Education of Young Physics Teacher, 2020)
The purpose of this study was to determine the effect and significance of the STAD learning model with mysterious card box media (kokami) on the physics learning outcomes of class VIII students on work and simple plane at SMP Negeri 1 Belitang Madang Raya in the 2020/2021 academic year. This research used quantitative research. The population in this study were all students of class VIII at SMP Negeri 1 Belitang Madang Raya, and the sample was selected by purposive sampling technique. In the experimental class, learning used the STAD learning model with kokami media, while in the control class, the learning used conventional models (lectures and questions and answers). Data collection techniques to determine the cognitive learning outcomes of students using a multiple-choice test with two tier question type, and hypothesis testing using the t-test. Based on the pretest and posttest results, the experimental class average score was higher than the control class average score. The pretest average score for the experimental class was 38, and the average score for the control class was 37. While the posttest average score for the experimental class was 75, and the control class was 63. The average results of the experimental class and control class were different, so that there is a significant influence between students whose learning uses the STAD learning model through kokami media with students whose learning used conventional model. It can be seen from the tcount which is greater than the ttable value, namely 14.4> 1.67, which means that H0 is rejected and Ha is accepted.